The Effect of Rabbit Urine and Cow Manure Application on The Growth and Yield of Centella asiatica L. - Firgiyanto, Refa; Kusparwanti, Tri Rini; Rohman, Fadil; Siswadi, Edi; Maulida, Maulida; Rahma, Sinta Dwi (AGRIUM: Jurnal Ilmu Pertanian, 2026)
Gotu kola (Centella asiatica L.) is a medicinal plant with high therapeutic potential, yet its cultivation in Indonesia remains underdeveloped. Excessive reliance on synthetic fertilizers poses risks to environmental sustainability and may negatively affect the quality of bioactive compounds. This study aimed to evaluate the effects of rabbit urine–based liquid organic fertilizer (LOF) and cow manure on the growth and yield of gotu kola, and to identify a sustainable fertilization strategy that supports vegetative development. The experiment was conducted using a factorial randomized group design with two factors: rabbit urine LOF concentrations (0, 100, and 200 ml/L) and cow manure dosages (0, 20, and 40 g/polybag), resulting in nine treatment combinations with three replications. Data were analyzed using analysis of variance. The results showed that rabbit urine LOF significantly influenced stolon length, with the 200 ml/L concentration consistently promoting longer stolon development compared to lower concentrations and the control. This response indicates that nutrients in rabbit urine, particularly nitrogen, enhance vegetative expansion through stolon growth. Other growth and yield parameters were not significantly affected, suggesting that the fertilization treatments primarily influenced early vegetative growth rather than yield formation. These findings demonstrate that integrating rabbit urine LOF with cow manure has potential as an environmentally friendly fertilization approach for sustainable gotu kola cultivation.